2019
DOI: 10.3389/fphar.2019.00452
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinic Acid and Nuclear Factor Erythroid 2-Related Factor 2 in Depression: Role in Neuroprogression

Abstract: Depression is an incapacitating neuropsychiatric disorder. The serotonergic system in the brain plays an important role in the pathophysiology of depression. However, due to delayed and/or poor performance of selective serotonin reuptake inhibitors in treating depressive symptoms, the role of the serotonergic system in depression has been recently questioned further. Evidence from recent studies suggests that increased inflammation and oxidative stress may play significant roles in the pathophysiology of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 96 publications
1
26
0
2
Order By: Relevance
“…Due to the role of inflammation in the development and progression of several disease states we hope these findings can increase the awareness of health professionals to the probability that SFA consumption will accelerate tryptophan catabolism via the kynurenine pathway creating a range of negative health sequelae. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Due to the role of inflammation in the development and progression of several disease states we hope these findings can increase the awareness of health professionals to the probability that SFA consumption will accelerate tryptophan catabolism via the kynurenine pathway creating a range of negative health sequelae. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Nrf2 attenuates the activation of NF-κB; this leads to suppression of the inflammasome activity by downregulating the expression of the inflammasome components NLRP3, caspase-1, and pro-IL-1β ( Li et al, 2008 ; Chu et al, 2019 ; Dang et al, 2019 ). In addition to its role in NLRP3 inflammasome, the Kea1-Nrf2 pathway is also involved in depression in preclinical and clinical studies ( Bansal et al, 2019 ; Chu et al, 2019 ; Dang et al, 2019 ; Swanson et al, 2019 ; Zborowski et al, 2020 ), which implies that interrupting the Keap1-NRF2 protein–protein interaction might be a potential therapy against depression. Furthermore, a recent animal study indicated that the Nrf2-NLRP3 signaling pathway, which is responsible for adjusting inflammation levels, plays a vital role in the depression induced by environmental factors ( Chu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NLRP3, the Kelch-like ECH associated protein 1(Keap1)/nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway is also involved in neuropathic pain and depression in preclinical and clinical studies ( Braidy et al, 2018 ; Li et al, 2018 ; Bansal et al, 2019 ; Chu et al, 2019 ; Dang et al, 2019 ; Swanson et al, 2019 ; Zborowski et al, 2020 ; Zhou et al, 2020a , 2020b ). Keap1 suppresses Nrf2 activity under physiological conditions, whereas Nrf2 is liberated from Keap1-mediated suppression on exposure to stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, an increase in QA concentration in the brain and cerebrospinal fluid of depressive individuals suffering from suicide was already found [48,49]. In addition, increased QA concentration has been associated with oxidative stress and lipid peroxidation [50].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 92%